Global journalism collaborations : worldwide storytelling projects in higher education - Blair, Katherine; Coomey, Marion; Sidlow, Faith (Abingdon, Oxon ; New York, NY : Routledge, 2024)
Global Journalism Collaborations offers guidance on detailed ways to create collaborative international projects in the communications and journalism fields -a hot topic in higher education. The chapters are contributed by professors and journalists from around the world. The authors explain, step-by-step, the process of collaborating with students and instructors at universities in dozens of countries in order to produce digital storytelling projects that are streamed worldwide. The book will inspire academics and students in any discipline to develop and create their own collaborative projects by sharing lessons learned through case studies of successful global collaborations. This truly interdisciplinary work will interest scholars and instructors of journalism, media studies, mass communication, higher education and anyone working on collaborative projects across a variety of disciplines.
Keywords: Journalism -- Study and teaching; Collaborative journalism -- Study and teaching; Intercultural communication -- Study and teaching; LANGUAGE ARTS & DISCIPLINES / Journalism; SOCIAL SCIENCE / Media Studies; EDUCATION / Higher